2009
DOI: 10.1080/10428190903147629
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome in patients with small intestinal non-Hodgkin lymphoma

Abstract: The clinical features and outcome of small intestinal lymphoma remain unclear. We retrospectively analyzed 23 patients who had non-Hodgkin lymphoma with a small intestinal lesion. With a median follow-up of 37 months, the 5-year overall survival and failure-free survival (FFS) were 64% and 60%, respectively. In a univariate analysis, a worse performance status at the start of treatment and the occurrence of abdominal symptoms or perforation during treatment were associated with poor survival. Perforation often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
27
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 26 publications
2
27
1
1
Order By: Relevance
“…The GI tract is the most common site of extranodal involvement in cases of non-Hodgkin's lymphoma (NHL), with an average incidence of 5-40% [1]. The stomach is the most common site of GI lymphoma (14-38%), followed by the small intestine [2,3]. NHL in the colorectal area, however, constitutes about 10-20% of all extranodal GI tract involvement [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…The GI tract is the most common site of extranodal involvement in cases of non-Hodgkin's lymphoma (NHL), with an average incidence of 5-40% [1]. The stomach is the most common site of GI lymphoma (14-38%), followed by the small intestine [2,3]. NHL in the colorectal area, however, constitutes about 10-20% of all extranodal GI tract involvement [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Considerable information on primary gastric DLBCL is available, but there are insufficient data on the clinical features and outcomes of primary intestinal DLBCL because it is usually studied as a subgroup of GI lymphomas. 1,[3][4][5] Although a few reports focusing on primary intestinal DLBCL have been published, [6][7][8][9] the sample sizes were small, and the optimal treatment strategies specific for primary intestinal DLBCL have not been established. Various treatment approaches have been tried, such as systemic chemotherapy similar to that used to treat nodal DLBCL and primary surgical resection of intestinal lesions and postoperative chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although unusual, the occurrence of perforations is potentially life threatening and leads to considerable morbidity from sepsis, multi-organ failure, prolonged hospitalization, complications of wound healing, delays in the initiation of chemotherapy and mortality. Several studies have reported an inferior outcome of GI lymphomas when complicated by perforation [2,4,5].…”
mentioning
confidence: 99%